Management Research and Grounded Theory - Graham J.J. Kenealy (Grounded Theory Review: An International Journal, 2008)
Grounded theory is a systematic methodology for the collection and analysis of data which was discovered by Glaser and Strauss in the 1960’s. The discovery of this method was first presented to the academic community in their book ‘The Discovery of Grounded Theory’ (1967) which still remains a primary point of reference for those undertaking qualitative research and grounded theory in particular. This powerful research method has become very popular in some research domains; whilst increasing in popularity it is still less prevalent in the field of organisational and management research particularly in its original form. This self reflexive paper sets out to explore the possibilities for this imbalance which takes the discussion onto the areas of methodological adaptation and training. It also enters the debate about access to research subjects and provides a succinct argument supporting the notion that grounded theory should simply be viewed as a method that develops empirically grounded conceptual theory.